UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PEPAYA JEPANG (Cnidoscolus aconnitifolius) METODE DIFUSI SILINDER - Septya Dwi Hartanti; Agus Purwanto; Angga Rahabistara Sumadji (Biospektrum Jurnal Biologi, 2023)
The leaves of the Japanese papaya plant (Cnidoscolus aconitifolius) contain active compounds of flavonoids, tannins, saponins, alkaloids and terpenoids which have the potential to have antibacterial activity. The aim of this research was to determine the antibacterial activity of Japanese papaya leaves against the test bacteria Staphylococcus aureus. The research was carried out through maceration extraction using 96% ethanol to obtain a thick extract. The antibacterial activity test was carried out using the diffusion cylinder method using sterile distilled water as a negative control while as a positive control using ciprofloxacin. Antibacterial activity was carried out through varying concentrations, namely 10%, 20% and 30%. The results of the study showed that Japanese papaya leaf extract with a concentration of 30% was more effective in inhibiting the growth of Staphylococcus aureus bacteria compared to 10% and 20% Japanese papaya leaf extract. The largest inhibition zone measurement at a concentration of 30% was 17.296 mm while concentrations of 10% and 20% were respectively 15,222 mm, and 13,018 mm.